Sanctus Amor (1908) Нины Петровской как жизнетворческий манифест - Samarin, Aleksey (Studia Rossica Posnaniensia, 2020)
Sanctus Amor is the only intravital storybook by Nina Petrovskaya, dedicated to Sergey Auslender. The title of the book, borrowed from the poem by Andrey Bely, initiates a literary polylogue addressed to several lovers of Petrovskaya: to Bely, as he once was her teacher of heavenly love; to Valery Bryusov, as he was Petrovskaya’s beloved one at the time of publication; to Auslender as the addressee of dedication and a new contender for being Petrovskaya’s favorite. Sanctus Amor represents the ideal of the Saintly Love, the manifesto which Petrovskaya followed rigorously in real life. Her letters to Bryusov and Vladislav Khodasevich reveal multiple congruences with the novels of Sanctus Amor, which demonstrate the inextricable character of life and literature in Petrovskaya’s worldview. The paper is devoted to the analysis of Sanctus Amor in the aspect of life-creating practices and its meaning in the literary dialogue with Auslender. Sanctus Amor is a complicated prescriptive symbolic message designed to proclaim its own, and to program another’s, concept of love.